Major Histocompatibility (B) Complex Gene Dose Effects on Rous Sarcoma Virus Tumor Growth - Tupick, T.A.; Bloom, S.E.; Jr., R.L. Taylor (International Journal of Poultry Science, 2005)
Major histocompatibility (B) complex (MHC) gene dose effects on Rous sarcoma outcome were examined using chickens aneuploid for the MHC-bearing chromosome. Six-week-old chickens were inoculated with subgroup A Rous sarcoma virus (RSV). Tumors were scored for size six times over a 10-wk period followed by assignment of a tumor profile index (TPI), which indicated the degree of tumor growth. In Experiment 1, matings between Line FCT-15 trisomic (B15B15B15) sires and dams produced disomic (B15B15), trisomic (B15B15B15), and tetrasomic (B15B15B15B15) progeny. The progressive tumor growth engendered by B15 did not differ significantly among the three B complex doses. In experiment 2, matings between UNH 193 (B19B19B19) trisomic parents produced progeny having 2, 3, and four B19 haplotype doses. Most Line 193 chickens regressed their tumors. However, disomic Line UNH 193 chickens had a significantly lower TPI than trisomic but not tetrasomic chickens. In experiment 3, Line UNH 193 was crossed with Line 6.15-5 (B5B5), a tumor progressor genotype, to produce either B5B19 or B5B19B19 genotypes. Mean tumor growth over time and mean TPI were significantly lower in B5B19B19 chickens compared with B5B19 chickens. These data indicate that B complex gene dose alterations for B15 did not affect Rous sarcomas but changes involving extra B19 doses enhanced tumor development. Furthermore, when combined with the progressive B5 haplotype, two doses of the tumor regressor-associated B19 haplotype were significantly more effective for inhibiting tumor development compared to one B19 dose.